2004
DOI: 10.1007/s00418-004-0676-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen free radicals and redox biology of organelles

Abstract: The presence and supposed roles of reactive oxygen species (ROS) were reported in literature in a myriad of instances. However, the breadth and depth of their involvement in cellular physiology and pathology, as well as their relationship to the redox environment can only be guessed from specialized reports. Whatever their circumstances of formation or consequences, ROS seem to be conspicuous components of intracellular milieu. We sought to verify this assertion, by collecting the available evidence derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(110 citation statements)
references
References 253 publications
(255 reference statements)
2
99
0
9
Order By: Relevance
“…It has been suggested that binding of high affinity peptide is accompanied by opening and closing of disulfide bonds either within class I (6,(77)(78)(79) or between ERp57 and tapasin in the loading complex (12). Because Ero1, the source of disulfide oxidizing equivalents, is restricted to the ER, conditions in the Golgi may be more reducing (80,81), and this could induce class I molecules to release their low affinity peptides prior to their return to the ER. Further work is needed to test these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that binding of high affinity peptide is accompanied by opening and closing of disulfide bonds either within class I (6,(77)(78)(79) or between ERp57 and tapasin in the loading complex (12). Because Ero1, the source of disulfide oxidizing equivalents, is restricted to the ER, conditions in the Golgi may be more reducing (80,81), and this could induce class I molecules to release their low affinity peptides prior to their return to the ER. Further work is needed to test these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial operation may be hampered not only by lack of oxygen as fi nal acceptor of electrons, but also for excessive proton pumping, which in the end may damage the mitochondrial membranes, alter the cytoplasmic redox equilibrium [36] and interfere with calcium and other ion signalling [37]. The action of uncoupling proteins may help protect the integrity of the system [38].…”
Section: Blood Flow and Oxygen Supplymentioning
confidence: 99%
“…It has long been recognized that high levels of free radicals or reactive oxygen species (ROS) can inflict direct damage to lipids. The primary sources of endogenous ROS production are the mitochondria, plasma membrane, endoplasmic reticulum, and peroxisomes (Moldovan and Moldovan, 2004). Lipid peroxidation or reaction of oxygen with unsaturated lipids produces a wide variety of oxidation products.…”
Section: Introductionmentioning
confidence: 99%